(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2013)
The present paper attempts to develop vulnerabilityprofiles of cities by highlighting exposure to various risks and hazards. Urbanrenewal interventions have been suggested in order to strengthen climateresilience of India’s urban centres. The paper shows that the resilient citiesare those that have sustainable infrastructure, efficient governance andinformed and capable citizens. This study shows trends across cities and theproblems with the approach to their development.